Handbook of real-world applications in modeling and simulation - Sokolowski, John A., 1953-; Banks, Catherine M., 1960- (Hoboken : John Wiley & Sons, 2012)
This handbook provides a thorough explanation of modeling and simulation in the most useful, current, and predominant applied areas, such as transportation, homeland security, medicine, operational research, military science, and business modeling. The authors offer a concise look at the key concepts and techniques of modeling and simulation and then discuss how and why the presented domains have become leading applications. The book begins with an introduction of why modeling and simulation is a reliable analysis assessment tool for complex syste.
Unstructured Surface MeshingUnstructured Tetrahedral Meshing; Acknowledgments; References; Chapter Eight: Military Interoperability Challenges; 8.1 Introduction and Learning Objectives; 8.2 Background; 8.3 Theory; 8.4 Live Virtual Constructive; 8.5 LVC Examples; 8.6 Distributed Simulation Engineering and Execution Process (DSEEP); 8.7 LVC Architecture Framework (LVCAF); 8.8 Simulation Systems; Summary; Key Terms; References; Index.
Includes bibliographical references and index.
Print version record.
Keywords: System analysis -- Mathematical models; Computer simulation; MATHEMATICS -- General; Computer science; SCIENCE -- System Theory; TECHNOLOGY & ENGINEERING -- Operations Research; Computer simulation; System analysis -- Mathematical models; Electronic books